Challenges Faced by Arts Graduates in the Current Job Market: A Sri Lankan Perspective - Mohamed Hasan Mohamed Majid; Mohammed Ibrahim Inthisar Banu (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Unemployment is a major issue for arts graduates in various countries, including Sri Lanka. In 2023, the Labor Force Survey reported an overall unemployment rate of 4.7%, with over 50,000 unemployed graduates, mostly from Arts and social sciences backgrounds in Sri Lanka. Therefore, the Sri Lankan government should develop appropriate policies to reduce unemployment. Consequently, research is needed to identify the factors and challenges faced by arts graduates in unemployment for policymakers. Numerous studies worldwide have explored the factors and challenges of unemployment among this group. The main objective of this study is to identify the challenges faced by arts graduates in the current Job market in Sri Lanka and to identify the causes of unemployment and propose recommendations to them. Quantitative research method was used to achieve the objectives of the study, the primary data were collected through a structured questionnaire administered to 120 Arts undergraduates from the South Eastern, Eastern, Peradeniya, and Jaffna Universities. Simultaneously, secondary data were gathered from books, research articles, University Grant Commission report, National Audit Office report, Sri Lanka Labor Force Survey report, and websites. The collected data was analyzed using Microsoft Excel. The study found that major challenges for Arts graduates include abundant job opportunities in the private sector. However, issues such as the necessary knowledge and skills often lead to prolonged unemployment. Many Arts graduates anticipate government jobs due to the perceived job security and pension benefits in the public sector. Simultaneously, Arts stream graduates who have completed professional courses and internship training are more likely to secure their first jobs immediately after graduation compared to those who haven't undergone such training. Nevertheless, a significant challenge is the limited employment opportunities for Arts graduates, both in the private and public sectors. The study indicates the necessity for substantial structural reforms on both the supply and demand sides to enhance the employability and employment rates of graduates. The government must take a leading role in these reforms to generate more job opportunities for arts graduates, while higher education institutes should initiate significant changes in study programs to cultivate intellectually rich and highly skilled graduates in arts and social sciences.